Distribution of evaluation scores for the models submitted to the second cryo-EM model challenge - Kryshtafovych, Andriy; Monastyrskyy, Bohdan; Adams, Paul D.; Lawson, Catherine L.; Chiu, Wah (Data in Brief, 2018)
142 protein structure models were submitted to second Cryo-EM model challenge (2015–2016). Accuracy of the models was evaluated with 54 evaluation scores. Results of the descriptive statistical analysis of the scores are provided in this article.